2020
DOI: 10.3390/foods9081036
|View full text |Cite
|
Sign up to set email alerts
|

Food and COVID-19: Preventive/Co-therapeutic Strategies Explored by Current Clinical Trials and in Silico Studies

Abstract: Foods, food ingredients, and their balanced consumption are recognized to have an important role in achieving or maintaining a state of wellbeing by acting as carriers of functional components and bioactive molecules. However, the potential contribution of foods to consumers’ health has so far only been partially exploited. The rapidly evolving scenario of the coronavirus disease 2019 (COVID-19) pandemic is stimulating profound reflection on the relationships between food and the etiological agent, the severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 99 publications
0
39
0
Order By: Relevance
“…Dietary fats induce dysbiosis and may increase intestinal permeability, inducing endotoxemia and chronic low-grade inflammation [ 192 ], whereas polyphenols modulate microbiota composition [ 186 ]. Although antiviral properties against SARS-CoV-2 (related to virus entry into the cells) have been reported in vitro for some bioactive phytochemicals ( Figure 1 ), including the hesperidin [ 193 , 194 ], quercetin [ 194 , 195 ], kaempferol [ 194 ], catechins [ 194 , 196 ], baicalin [ 197 ], curcumin [ 194 ] and resveratrol [ 194 ], their availability in humans is low [ 198 ]. Only 5–10% of dietary polyphenols can be absorbed and they undergo to microbial metabolism in the colon [ 188 ].…”
Section: Mechanisms Of the Mediterranean Diet Componentsmentioning
confidence: 99%
“…Dietary fats induce dysbiosis and may increase intestinal permeability, inducing endotoxemia and chronic low-grade inflammation [ 192 ], whereas polyphenols modulate microbiota composition [ 186 ]. Although antiviral properties against SARS-CoV-2 (related to virus entry into the cells) have been reported in vitro for some bioactive phytochemicals ( Figure 1 ), including the hesperidin [ 193 , 194 ], quercetin [ 194 , 195 ], kaempferol [ 194 ], catechins [ 194 , 196 ], baicalin [ 197 ], curcumin [ 194 ] and resveratrol [ 194 ], their availability in humans is low [ 198 ]. Only 5–10% of dietary polyphenols can be absorbed and they undergo to microbial metabolism in the colon [ 188 ].…”
Section: Mechanisms Of the Mediterranean Diet Componentsmentioning
confidence: 99%
“…Evidently, in 2003, patients who suffered from severe acute respiratory syndrome (SARS) and received Traditional Chinese Medicine (TCM) treatment were reported to have short-term hospitalization (inpatient care), reduced steroid-related side effects, and improvement from the viral symptoms ( World Health Organization, 2004 ). Thus, most previous publications including review papers have mainly focused on the use of TCM and other ethnobotanical herbs ( Dudani and Saraogi, 2020 ; Khanna et al, 2020 ; Ling, 2020 ; Vellingiri et al, 2020 ) or the use of drugs and other dietary supplements that are currently in clinical trials ( Di Matteo et al, 2020 ; Kumar et al, 2020 ; Stahlmann and Lode, 2020 ). This may not cover most, if not all, potential plant species or extracts available globally.…”
Section: Introductionmentioning
confidence: 99%
“…extract could exhibit immunostimulatory effect which may aid to suppress the coronavirus infection. Various other studies have also shown that diets including micronutrients such as vitamin C and D have the potential to prevent or treat COVID-19 by fortifying immune system, some of which have entered clinical trial phase ( Di Matteo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of effective curative treatments and validated vaccines, there is an urgent need for innovative solutions. Combining conventional medical treatments with nutritional interventions represents one such solution, which is gaining traction [2,3]. Considerable recent efforts have been directed towards identifying new purposes, or alternative uses, for existing drugs (so-called "drug repurposing") [4,5].…”
Section: Introductionmentioning
confidence: 99%